Circuit analysis theory and practice - Robbins, Allan; Miller, Wilhelm (Cengage Learning, 2013)
This work provides coverage of circuit analysis topics, including fundamentals of DC and AC circuits, methods of analysis, capacitance, inductance, magnetism, simple transients and computer methods.